Social Hierarchy and Mortuary Variability: The Iron Age Culture of Peninsular India with Special Reference to Kerala - Jenee Peter
The concept of Iron Age in southern India is reviewed here based on recently discovered archaeological sites in Kerala. Sites provide vital clues for iron‐making, iron‐working and lithic tools. It shows that Iron Age covers a wide chronological bracket from late prehistoric to early historic periods. There is a marked change from prehistoric social formations with the introduction of iron. Its two phases, Early Iron Age and Late Iron Age can be broadly identified with the Megalithic and Early Historic periods respective ly. Textual and material evidences indicate that during Late Iron Age the peninsular Indian coast participated in Indian Ocean trade network and urban sites in middle Ganga valley and peninsular India seem to have interacted regularly with each other. Iron technology fuelled a visible change in the cultural past of Kerala. The megalithic mortuary practices are indicators of social variability during Iron Age and maritime trade changed the social makeup in coastal Kerala during Late Iron Age.